(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The article examines the synthesis of artistic attitude and semantic essence on the example of Oydinniso’s poetry. It observes the uniqueness of poetic interpretation, the connection between image and expression, the integrity of form and content in lyrics, the degree of emotional realization, the depth of philosophical generalization, the overlap of emotional competence and aesthetic ideal. In fact, the principles of creativity serve to indicate the individual dimension of the poet’s worldview and the analogy of the materialization of imagination.